Current advances in cancer vaccines targeting NY-ESO-1 for solid cancer treatment - Zhou, Hong; Ma, Yipeng; Liu, Fenglan; Li, Bin; Qiao, Dongjuan; Ren, Peigen; Wang, Mingjun (Frontiers in Immunology, 2023)
New York-esophageal cancer 1 (NY-ESO-1) belongs to the cancer testis antigen (CTA) family, and has been identified as one of the most immunogenic tumor-associated antigens (TAAs) among the family members. Given its ability to trigger spontaneous humoral and cellular immune response and restricted expression, NY-ESO-1 has emerged as one of the most promising targets for cancer immunotherapy. Cancer vaccines, an important element of cancer immunotherapy, function by presenting an exogenous source of TAA proteins, peptides, and antigenic epitopes to CD4+ T cells via major histocompatibility complex class II (MHC-II) and to CD8+ T cells via major histocompatibility complex class I (MHC-I). These mechanisms further enhance the immune response against TAAs mediated by cytotoxic T lymphocytes (CTLs) and helper T cells. NY-ESO-1-based cancer vaccines have a history of nearly two decades, starting from the first clinical trial conducted in 2003. The current cancer vaccines targeting NY-ESO-1 have various types, including Dendritic cells (DC)-based vaccines, peptide vaccines, protein vaccines, viral vaccines, bacterial vaccines, therapeutic whole-tumor cell vaccines, DNA vaccines and mRNA vaccines, which exhibit their respective benefits and obstacles in the development and application. Here, we summarized the current advances in cancer vaccines targeting NY-ESO-1 for solid cancer treatment, aiming to provide perspectives for future research.